2010
DOI: 10.1074/jbc.m109.085225
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of VACM-1/Cul5 by Protein Kinase A Regulates Its Neddylation and Antiproliferative Effect

Abstract: Expression of the VACM-1/cul5 gene in endothelial and in cancer cell lines in vitro inhibits cellular proliferation and decreases phosphorylation of MAPK. Structure-function analysis of the VACM-1 protein sequence identified consensus sites specific for phosphorylation by protein kinases A and C (PKA and PKC) and a Nedd8 protein modification site. Mutations at the PKA-specific site in VACM-1/Cul5 ( S730A VACM-1) sequence resulted in increased cellular growth and the appearance of a Nedd8-modified VACM-1/Cul5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…In addition to the important mechanistic studies of CUL5 that have been reported from the laboratory of Dr Burnatowska-Hledin since their initial discovery of CUL5 in 2000 ( 18 20 ), two other studies have demonstrated a regulatory role for two miRNAs, one, for miR-19a and miR-19b, in cervical cancer and another, for miR-7, in hepatocellular cancer ( 4 , 5 ). We searched miRNA target prediction algorithms for CUL5 and discovered that several, including TargetScan and PicTar, indicated that miR-182 was an even higher confidence prediction than either of the others.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the important mechanistic studies of CUL5 that have been reported from the laboratory of Dr Burnatowska-Hledin since their initial discovery of CUL5 in 2000 ( 18 20 ), two other studies have demonstrated a regulatory role for two miRNAs, one, for miR-19a and miR-19b, in cervical cancer and another, for miR-7, in hepatocellular cancer ( 4 , 5 ). We searched miRNA target prediction algorithms for CUL5 and discovered that several, including TargetScan and PicTar, indicated that miR-182 was an even higher confidence prediction than either of the others.…”
Section: Discussionmentioning
confidence: 99%
“…Cul5(S730A) accelerates cellular proliferation and induces angiogenic growth in rat adrenal medullary endothelial cells (RAMECs) [ 19 ]. Cul5 neddylation is increased by the S730A mutation, and activation of PKA by forskolin suppresses the neddylation of Cul5 [ 20 ]. Furthermore, PKC-induced RAMEC proliferation is enhanced by Cul5(S730A) [ 20 ].…”
Section: Identification and Regulation Of Cullinmentioning
confidence: 99%
“…Cul5 neddylation is increased by the S730A mutation, and activation of PKA by forskolin suppresses the neddylation of Cul5 [ 20 ]. Furthermore, PKC-induced RAMEC proliferation is enhanced by Cul5(S730A) [ 20 ]. Cul5(S730A) expression in RAMECs increases the levels of phosphorylated MAPK and the translocation of the transcription factor EGR-1, a tumor suppressor, to the nucleus; it also causes morphological alterations mediated by actin rearrangement [ 19 ].…”
Section: Identification and Regulation Of Cullinmentioning
confidence: 99%
“…Although not studied here, the possibility that resveratrol regulates VACM-1 protein modification and/or stability should also be considered. It is now accepted that in order to activate the E3 ligases all cullins must be modified by a ubiquitin like protein called Nedd8 (review in Saha and Deshaies, 2008) and we have shown that the antiproliferative effect of VACM-1/cul5 is clearly affected by such modification (Buchwalter et al 2008, Bradley et al, 2010. Unfortunately, the role of Nedd8 in VACM-1/cul5-dependent regulation of resveratrol activity was not studied here.…”
Section: Resultsmentioning
confidence: 82%